Utilization of LDPE Plastic Waste, Coconut Shell and Coconut Husk as Basic Material for Briquettes with Tapioca Starch Adhesive - Sheilla Rully Anggita; Renanda Fasha Devarasalya; Istikomah Istikomah; Ari Bawono (Jurnal Ilmu Fisika, 2023)
Bio-briquettes of organic waste can be used as alternative energy to solve the waste problem. This study aimed to determine the quality of bio-briquettes made of LDPE, coconut husk, and coconut shell with tapioca adhesive. The coconut husk and shell were carbonized at 300 °C for 60 minutes. Charcoal that has been ground and sieved with 40 mesh is mixed with tapioca flour adhesive, and pieces of LDPE are added. Then, the sample is pressed with a cylindrical mold with a matrix strength of 5 tons. Bio-briquettes were dried in an oven at 80 °C for 12 hours. The quality of the briquette was evaluated through proximate analysis, including the calorific value, moisture content, ash content, volatile matter content, and fixed carbon content. The calorific value of all samples complied with the regulation of the Ministry of Energy and Mineral Resources (ESDM) No. 047 of 2006, which is above 4400 cal/g. The maximum moisture content is 15%, which fulfills SNI 06–3730-1995 standards, and the ESDM regulation, especially for the composition of 40% shell: 40% coconut: LDPE 20%. The ash content, volatile matter content, and fixed carbon content of all samples did not comply with SNI briquette standards and ESDM regulations.